Hiding in Plain Sight: Interplay between Staphylococcal Biofilms and Host Immunity - Scherr, Tyler D.; Heim, Cortney E.; Morrison, John M.; Kielian, Tammy (Frontiers in Immunology, 2014)
S. aureus and S. epidermidis are notable for their propensity to form biofilms on implanted medical devices. Staphylococcal biofilm infections are typified by their recalcitrance to antibiotics and ability to circumvent host immune-mediated clearance, resulting in the establishment of chronic infections that are often recurrent in nature. Indeed, the immunomodulatory lifestyle of biofilms seemingly shapes the host immune response to ensure biofilm engraftment and persistence in an immune competent host. Here, we provide a brief review of the mechanisms whereby S. aureus and S. epidermidis biofilms manipulate host-pathogen interactions and discuss the concept of microenvironment maintenance in infectious outcomes, as well as speculate how these findings pertain to the challenges of staphylococcal vaccine development.